Pengaruh Pendidikan Seksual Dengan Peningkatan Pengetahuan Tentang Pencegahan Kekerasan Seksual Pada Siswa Kelas 5 Dan 6 Di SDN 104 Rejang Lebong Tahun 2024 - Istiqoma, Putri Sonia; Murwati, Murwati; Aprianti, Delta (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Sexual violence against children continues to be a concern in Indonesia. In 2022, there were more than 14,500 cases of sexual violence against children (KemenPPPA). That number decreased to 6,198 cases in 2023, but sexual violence remains one of the most prevalent forms of violence. As of 2024, cases of sexual violence against children, including in Rejang Lebong Regency, Bengkulu, continue to occur. This study aims to determine the effect of sexual education on increasing knowledge of fifth and sixth-grade students at SDN 104 Rejang Lebong about sexual violence prevention. This study used a quasi-experimental design with a pretest-posttest one-group design. 38 students were selected as samples using stratified random sampling. Data were collected through questionnaires filled out before and after the intervention, which consisted of sexual education using animated video media. The results showed that before receiving sexual education, most students had a sufficient level of knowledge (52.6%). After the intervention, there was an increase, with 60.5% of students achieving a good level of knowledge. The Wilcoxon test results showed p-value of 0.000 (p<0.05), indicating a significant effect of sexual education on improving students' knowledge about sexual violence prevention. These findings indicate that sexual education through animated video media can be an effective method for improving students' understanding. Therefore, sexual education should be integrated into the school curriculum as a preventive measure to protect children from the risk of sexual violence.